technique of multi attribute decision making in an election medicine by using simple additive weighting (SAW) and analytical hierarchy process (AHP) method for skin diseases survivor - TIJANIYAH TIJANIYAH (Jurnal Arus Elektro Indonesia, 2016)
In generally, giving some medicines for a patient must use doctor’s recipe. Author has done different research with generally the case that is about giving some medicines without doctor’s recipe specially for skin disease. Drug selection can be done by a pharmacist namely self medication. Pharmacy duty medicine, definite medicine, free medicine and strong medicine that can only be given by a pharmacist. The medicine selection is applying to decision support system with simple additive weighting (SAW) and analytical hierarchy process (AHP) method. From the best result dan accurate proved to use SAW method because the comparasion result point to error level of final result, extrapolation process, the puporse of algoritm to decide a alternative and compatibility level of pharmacist recipe data with the result data of decision support system.